2015
DOI: 10.1016/j.susc.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lithium–sulfur battery discharge products through 6Li and 33S solid-state MAS and 7Li solution NMR spectroscopy

Abstract: Li and 33 S solid-state magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy were used to identify the discharge products in lithium-sulfur (Li-S) battery cathodes. Cathodes were stopped at different potentials throughout battery discharge and measured ex-situ to obtain chemical shifts and T 2 relaxation times of the products formed. The chemical shifts in the spectra of both 6 Li and 33 S NMR demonstrate that long-chain, soluble lithium polysulfide species formed at the beginning of discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 43 publications
(84 reference statements)
3
57
0
Order By: Relevance
“…The identifi cation of the formation of these species is important to understand the Li-S redox reactions, as some researchers attribute the capacity fading in Li-S cell to the formation of an insulating Li 2 S layer on the cathode. [ 16,25,154 ] However, XRD results were controversial regarding the formation of crystalline Li 2 S during discharge [ 23,25,124,155 ] and the reappearance of sulfur. [ 23,58,123,156 ] Recently, several in-situ XRD studies on the sulfur electrode during charge and discharge agreed on the formation of Li 2 S during discharge and its conversion to crystalline S 8 during the following charge.…”
Section: Identifi Cation Of the Formation Of LI 2 S And Re-depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identifi cation of the formation of these species is important to understand the Li-S redox reactions, as some researchers attribute the capacity fading in Li-S cell to the formation of an insulating Li 2 S layer on the cathode. [ 16,25,154 ] However, XRD results were controversial regarding the formation of crystalline Li 2 S during discharge [ 23,25,124,155 ] and the reappearance of sulfur. [ 23,58,123,156 ] Recently, several in-situ XRD studies on the sulfur electrode during charge and discharge agreed on the formation of Li 2 S during discharge and its conversion to crystalline S 8 during the following charge.…”
Section: Identifi Cation Of the Formation Of LI 2 S And Re-depositionmentioning
confidence: 99%
“…[ 20 ] The technique of 7 Li NMR has the capability to distinguish solid vs. dissolved products containing Li + and can detect small crystallites containing Li and S with low X-ray scattering signals. However, the work done by Huff et al using 6 Li and 33 S magic angle spinning (MAS) NMR demonstrated that Li 2 S is produced only at the end of the discharge in cathodes discharged to 1.5 V. [ 154 ] The contradictions in these studies can be attributed to the complexity of the Li-S system, Adv. Energy Mater.…”
Section: Identifi Cation Of the Formation Of LI 2 S And Re-depositionmentioning
confidence: 99%
“…Also 33 S NMR has been used in LSB study because of its large quadrupole moment, the low natural abundance (0.8%), and low receptivity. Therefore, in situ NMR spectroscopy can provide critical real‐time information about anode lithium‐dendrite growth, LPS formation, and sequential migration in the LSB research field …”
Section: Technique Reviewmentioning
confidence: 99%
“…In situ NMR spectroscopy has also provided insights into the complex electrochemistry of LPS formation in the LSB system, especially in tracking transient reactions during cycling . Huff et al investigated the reduction products of an LSB cell with a cathode (4.29 wt% sulfur showing the initial capacity of 1550 mA g −1 at 0.4C) in an electrolyte (1 m LiTFSI in 1:1 DOL:DME) by in situ NMR spectroscopy. They found that Li 2 S is exclusively produced at the end of an LSB discharge event (1.5 V), along with the formation of small amounts of longer‐chain LPS species.…”
Section: Technique Reviewmentioning
confidence: 99%
See 1 more Smart Citation